Using QSPM and WASPAS methods for determining outsourcing strategies - Lashgari, Shima; Antuchevičienė, Jurgita (Journal of Business Economics and Management, 2014)
The aim of the current study is to select the best strategies for outsourcing development, applying decision-making tools that enable to make reasoned decision. To evaluate outsourcing strategies, a new model of Comprehensive Framework for Strategy Formulation and Selection is presented. Development of outsourcing of healthcare services in Tehran is analysed in the paper. Strengths, Weaknesses, Opportunities, and Threats analysis is used to evaluate the internal and external factors affecting the outsourcing of healthcare services in health deputy of the Tehran University of Medical Sciences in different aspects and to develop several possible outsourcing strategies. Quantitative Strategic Planning Matrix is applied for quantitative evaluation of strategies. It is proposed to validate the approach by applying Multiple Criteria Decision Making methods. Robust and accurate Weighted Aggregated Sum Product Assessment method is selected and applied for quantitative evaluation of strategies. Based on the consistency of the results of the both approaches, the five best strategies to develop healthcare services outsourcing are offered. First published online: 29 Apr 2014